Report of a case of papillary thyroid carcinoma in association with Hashimoto's thyroiditis - Okani, Chukwudi Onyeaghana (Niger Med J, 2015)
Hashimoto thyroiditis (HT) is an autoimmune disease, known to be the most common cause of hypothyroidism in nonendemic goitrous areas. It is usually characterized by symmetric, painless, and diffused but sometimes localized swelling of the thyroid gland with features of hypothyroidism. Papillary thyroid carcinoma (PTC), on the other hand, is the most common yet less aggressive form of thyroid cancer, especially in iodine-deficient areas. The coexistence of the two diseases is possible but not common. This case study reports a 50-year-old female with a 10-year history of a huge goiter, which was essentially symptom-free until about 3 months prior to presentation when the patient started complaining of neck pain, dysphagia, productive cough, and cold intolerance. Physical examination revealed focal cystic and tender area in the multinodular swelling and associated cervical lymphadenopathy on the left side of the neck. The serum thyroid stimulating hormone was high, sub-normal T3, and the T4 was low. The fine needle aspiration cytology yielded 10 ml of aspirate of pus admixed with altered blood which on microscopy showed a few suspicious follicular epithelial cells with open nuclei admixed with mainly neutrophil polymorphs, siderophages, and foam cells in a hemorrhagic background. The patient had an incision biopsy that showed areas displaying PTC and HT.